2021
DOI: 10.1021/acsami.0c20012
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Solubility of Poly(vinylphenothiazine) in Carbonate-Based Battery Electrolytes

Abstract: Organic materials are promising candidates for next-generation battery systems. However, many organic battery materials suffer from high solubility in common battery electrolytes. Such solubility can be overcome by introducing tailored high-molecular-weight polymer structures, for example, by crosslinking, requiring enhanced synthetic efforts. We herein propose a different strategy by optimizing the battery electrolyte to obtain insolubility of non-cross-linked poly(3-vinyl-N-methylphenothiazine) (PVMPT). Succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 68 publications
3
51
0
Order By: Relevance
“…For both polymers, the specific current values significantly decreased after the initial cycle, which indicates a dissolution of the active material in the battery electrolyte upon oxidation. Most of this occurred during the first cycle, but the current values slowly further decreased upon cycling . This is in accordance with former studies on PVMPT -based composite electrodes where the current loss was correlated with UV/vis spectroscopic investigations, and the electrolyte solution was deeply colored. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For both polymers, the specific current values significantly decreased after the initial cycle, which indicates a dissolution of the active material in the battery electrolyte upon oxidation. Most of this occurred during the first cycle, but the current values slowly further decreased upon cycling . This is in accordance with former studies on PVMPT -based composite electrodes where the current loss was correlated with UV/vis spectroscopic investigations, and the electrolyte solution was deeply colored. , …”
Section: Resultssupporting
confidence: 91%
“…We could circumvent this dissolution by cross-linking the polymer to X-PVMPT , which allowed access to almost the full theoretical specific capacity of 112 mAh g –1 , corresponding to a one-electron oxidation of each phenothiazine subunit . We recently showed that changing the electrolyte solvent from EC/DMC (1:1) to EC/EMC (3:7) also led to an insolubility of PVMPT in both states B and C , thereby unlocking its full specific capacity paired with a high rate capability and low self-discharge . A change in the heteroatom within the heterocyclic ring system from S to O in poly­(3-vinyl- N -methylphenoxazine) or using a poly­(norbornene) backbone had reduced the π-interactions between the redox-active groups and provided an indication that the molecular structure of the poly­(vinylene) PVMPT is an ideal prerequisite for such interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The most well‐known p‐type organic cathode materials are conducting polymers (e. g., polyaniline, [11,12] polytriphenylamine, [13] and polypyrrole [14] ) and nitroxyl radical polymers (e. g., PTMA [15] ). In recent years, researchers’ interest also shifts to polymers based on various electroactive heteroaromatics, including N ‐substituted phenazine, [16–19] conjugated pyridine dimer, [20] phenothiazine, [18,21–31] phenoxazine, [32] and thianthrene [33,34] . A merit of these heteroaromatic units is that they are potentially able to deliver two electrons and thus achieve attractive capacity above 200 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these heteroaromatic units, phenothiazine (PTZ) is the most affordable for large‐scale applications and different polymerization methods have been attempted for it. For example, the PTZ units can be hanged as pendants on a robust polymer chain (e. g., PVMPT, [21–23] PVBPT, [25] and PNMPT [27] ), linearly connected or cross‐linked through cross coupling reaction (e. g., poly‐ N ‐propylphenothiazine [28] and HPPT [29] ) or copolymerized with other p‐type units (e. g., P1b [30] and PT‐DMPD [31] ). Although these studies provide general understanding about the redox behavior of PTZ‐based polymers, the reversible capacities are far away from satisfaction as only few exceed 100 mAh g −1 even at the cost of complicated synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Solubility of supercritical CO 2 in polymers is the key factor affecting the performance of foamed materials and also widely used in the extraction and separation of various chemicals and the preparation and modification of new materials, displaying good prospects in theoretical research and application [1][2][3][4][5][6]. Under the supercritical conditions of high temperature and high pressure, the dissolution behaviour is affected by many factors and shows nonlinear, non-equilibrium, dynamic and critical properties, which result in the difficulty in the study of dissolution experiments [7][8][9][10][11][12][13][14][15]. The current information technology and artificial intelligence have provided theoretical and technical support for the calculation and simulation of material properties.…”
Section: Introductionmentioning
confidence: 99%